Review HR Perspective toward the Role of Multinational Corporations (MNCs) in Thailand - Sineenat Suasungnern; Nico Irawan; Atchara Salee; Ada Marie Gallego Mascarinas (Kontribusia : Research Dissemination for Community Development, 2018)
The study is using a qualitative strategy to describe the HR perspective towards the Role of Multinational Corporations (MNCs) in Thailand by using the pervious instrumental study review. Then, the data was classified into three parts: Part I: MNCs in developing countries; Part II: Overview the context of Thailand; Part III: Review the Role of MNCs in Thailand from the HR Perspective. As Thailand is a developing country which takes into account of globalization activities, hence, MNCs play an important role to enhance the level of economic growth. The developing countries must improve their infrastructure and skilled workers to be reach the competitive advantage among region and attractive to foreign direct investments. The result of the study showed the characteristics in social context in Thailand, how the beliefs of Thai society impact ethical behavior, attitude in business and implications of HR practices. Thai political context is identified the situation of replacement employees. The study describe that the qualification require has go to foreigners rather than Thai workers. Thai labor laws has identified the inequality of Social Security Circumstances between private sector, agricultural workers, and public employees. and the role of MNCs in Thailand from the HR perspective. It shows that HRD systems must be able to enhance and build a quality program to put people to work.